87.8k views
4 votes
Simlify the expression 4^3 +(3 - 2).

User Punkouter
by
4.0k points

2 Answers

9 votes

Answer:


65

Explanation:

Firstly, you have to Simplify what's inside the parentheses.

and that is 3-2 = 1.


{4}^(3) + 1

Secondly, you have to Simplify 4³ to 64. 4 to the power of 3 is 64.


64 + 1

And lastly, you have to simplify 64 + 1. which is.


65

Therefor, the answer is, 65.

User Askar Kalykov
by
4.8k points
4 votes

Answer:

The answer is 65

Explanation:

3-2 = 1

4^3 = 64

64+1 = 65

Hope this helps.

User Iridio
by
4.8k points